Relationship between Occupational Stress and Mental Health in Male Personnel of Medical Emergency in Golestan Province - Zahra Moshtagh Eshgh; Ali Akbar Aghaeinejad; Akram Peyman; Aref Amirkhani; Maryam Chehregosha (Golestan University of Medical Sciences, 2015)
Background and Objective: One of the environmental factors bringing about chronic stress is something that is related to occupation. Because mental health improvement of a society particularly in a productive group is a necessity for dynamics and progression of a community, we aimed to examine the relationship between occupational stress and mental health in medical emergency's Male staff of Golestan province, 2012-2013. Material and Methods: This correlational study was conducted, via census method, 206 pre-hospital personnel working in 44 emergency stations. The instruments were demographic checklist, Occupational stress questionnaire for nurses and Goldberg general health questionnaire. The data was analyzed by descriptive statistics, Pearson correlation coefficient, ANOVA, T-test, and Tukey Test, using SPSS 16 software. Results: One hundred and seventeen (75.5%) of emergency staff had a medium to high level of occupational stress and 145 of them (75.1%) a medium to low level of mental health. A significant inverse relationship was seen between the overall level of occupational stress and mental health. Occupational stress was significantly associated with the variables such as age and type of employment, and mental health with type of employment. Conclusion: Occupational stress can adversely affect clinical practice and mental health in pre-hospital personnel. Hence, the use of some strategies to reduce stress can improve the mental health in that it leads to increase the quality of nursing care.